2011 White Paper on Recent Issues in Bioanalysis and Regulatory Findings from Audits and Inspections. (September 2011) - Garofolo, Fabio; Rocci, Mario L; Dumont, Isabelle; Martinez, Suzanne; Lowes, Steve; Woolf, Eric; van Amsterdam, Peter; Bansal, Surendra; Barra, Ariadna Cristina Gomes; Bauer, Ronald; Booth, Brian P; Carrasco-Triguero, Montserrat; et al.
The 5th Workshop on Recent Issues in Bioanalysis (WRIB) was organized by the Calibration and Validation Group as a 2-day full immersion workshop for pharmaceutical companies, CROs and regulatory agencies to discuss, review, share perspectives, provide potential solutions and agree upon a consistent approach to recent issues in the bioanalysis of both small and large molecules. High quality, better compliance to regulations and scientific excellence are the foundation of this workshop. As in the previous editions of this significant event, recommendations were made and a consensus was reached among panelists and attendees, including industry leaders and regulatory experts representing the global bioanalytical community, on many 'hot'' topics in bioanalysis. This 2011 White Paper is based on the conclusions from this workshop, and aims to provide a practical reference guide on those topics.